Cyclopia extracts act as selective estrogen receptor subtype downregulators in estrogen receptor positive breast cancer cell lines: Comparison to standard of care breast cancer endocrine therapies and a selective estrogen receptor agonist and antagonist - Olayoku, Folasade R.; Verhoog, Nicolette J. D.; Louw, Ann (Frontiers in Pharmacology, 2023)
Breast cancer is the most diagnosed type of cancer amongst women in economically developing countries and globally. Most breast cancers express estrogen receptor alpha (ERα) and are categorized as positive (ER+) breast cancer. Endocrine therapies such as, selective estrogen receptor modulators (SERMs), aromatase inhibitors (AIs), and selective estrogen receptor down-regulators (SERDs) are used to treat ER+ breast cancer. However, despite their effectiveness, severe side-effects and resistance are associated with these endocrine therapies. Thus, it would be highly beneficial to develop breast cancer drugs that are as effective as current therapies, but less toxic with fewer side effects, and less likely to induce resistance. Extracts of Cyclopia species, an indigenous South African fynbos plant, have been shown to possess phenolic compounds that exhibit phytoestrogenic and chemopreventive activities against breast cancer development and progression. In the current study, three well characterized Cyclopia extracts, SM6Met, CoT and P104, were examined for their abilities to modulate the levels of the ER subtypes, ERα and ERβ, which have been recognized as crucial to breast cancer prognosis and treatment. We showed that the Cyclopia subternata Vogel (C.subternata Vogel) extracts, SM6Met and CoT, but not the C.genistoides extract, P104, reduced ERα protein levels while elevating ERβ protein levels, thereby reducing the ERα:ERβ ratio in a similar manner as standard of care breast cancer endocrine therapies such as fulvestrant (SERD) and 4-hydroxytamoxifen (SERM). ERα expression enhances the proliferation of breast cancer cells while ERβ inhibits the proliferative activities of ERα. We also showed that in terms of the molecular mechanisms involved all the Cyclopia extracts regulated ERα and ERβ protein levels through both transcriptional and translational, and proteasomal degradation mechanisms. Therefore, from our findings, we proffer that the C.subternata Vogel extracts, SM6Met and CoT, but not the C.genistoides extract, P104, selectively modulate ER subtypes levels in a manner that generally supports inhibition of breast cancer proliferation, thereby demonstrating attributes that could be explored as potential therapeutic agents for breast cancer.